Emotional experiences and psychological well-being in 51 countries during the covid-19 pandemic - Sun, Rui; Balabanova, Alisa; Bajada, Claude Julien; Liu, Yang; Kriuchok, Mariia; Voolma, Silja-Riin; Đurić, Mirna; Mayer, Claude-Hélène; Constantinou, Maria; Chichua, Mariam; Li, Chengcheng; Foster-Estwick, Ashley; et al. (American Psychological Association, 2024)
The COVID-19 pandemic presents challenges to psychological well-being, but how can we predict when people suffer or cope during sustained stress? Here, we test the prediction that specific types of momentary emotional experiences are differently linked to psychological well-being during the pandemic. Study 1 used survey data collected from 24,221 participants in 51 countries during the COVID-19 outbreak. We show that, across countries, well-being is linked to individuals’ recent emotional experiences, including calm, hope, anxiety, loneliness, and sadness. Consistent results are found in two age, sex, and ethnicity-representative samples in the United Kingdom (n = 971) and the United States (n = 961) with preregistered analyses (Study 2). A prospective 30-day daily diary study conducted in the United Kingdom (n = 110) confirms the key role of these five emotions and demonstrates that emotional experiences precede changes in well-being (Study 3). Our findings highlight differential relationships between specific types of momentary emotional experiences and well-being and point to the cultivation of calm and hope as candidate routes for well-being interventions during periods of sustained stress.